Antegrade persufflation of porcine kidneys improves renal function after warm ischemia - Min, Catherine; Galons, Jean-Philippe; Lynch, Ronald M.; Steyn, Leah V.; Price, Nicholas D.; Weegman, Brad P.; Taylor, Michael J.; Pandey, Abhishek; Harland, Robert; Martin, Diego; Besselsen, David; Putnam, Charles W.; et al. (Frontiers in Transplantation, 2024)
IntroductionTransplantation of kidneys from expanded criteria donors (ECD), including after circulatory death (DCD), is associated with a higher risk of adverse events compared to kidneys from standard criteria donors. In previous studies, improvements in renal transplant outcomes have been seen when kidneys were perfused with gaseous oxygen during preservation (persufflation, PSF). In the present study, we assessed ex-vivo renal function from a Diffusion Contrast Enhanced (DCE)-MRI estimation of glomerular filtration rate (eGFR); and metabolic sufficiency from whole-organ oxygen consumption (WOOCR) and lactate production rates.MethodsUsing a porcine model of DCD, we assigned one kidney to antegrade PSF, and the contralateral kidney to static cold storage (SCS), both maintained for 24 h at 4°C. Post-preservation organ quality assessments, including eGFR, WOOCR and lactate production, were measured under cold perfusion conditions, and biopsies were subsequently taken for histopathological analysis.ResultsA significantly higher eGFR (36.6 ± 12.1 vs. 11.8 ± 4.3 ml/min, p < 0.05), WOOCR (182 ± 33 vs. 132 ± 21 nmol/min*g, p < 0.05), and lower rates of lactate production were observed in persufflated kidneys. No overt morphological differences were observed between the two preservation methods.ConclusionThese data suggest that antegrade PSF is more effective in preserving renal function than conventional SCS. Further studies in large animal models of transplantation are required to investigate whether integration with PSF of WOOCR, eGFR or lactate production measurements before transplantation are predictive of post-transplantation renal function and clinical outcomes.